Adding Dry Needling to Post-Isometric Relaxation Reduces Pain and Disability in Office Workers with Non-Specific Neck Pain - Kurniantara, I Made Buda (PT Inovasi Pratama Internasional, 2025)
Non-specific neck pain in office workers has increased due to changes in work habits after the pandemic. Manual therapy approaches such as Post-Isometric Relaxation (PIR) and Dry Needling (DN) are promising but lack sufficient research support. This study aims to evaluate the effects of PIR combined with DN, as well as compare DN with PIR alone. This experimental study employed a randomized two-group pre-test-post-test design. The intervention group (IG) received DN in addition to PIR, while the control group (CG) received only PIR. Each group comprised 16 participants. The study was conducted over two weeks, with three PIR sessions and two DN sessions per week. Measurements using the Numerical Pain Rating Scale (NPRS) and the Neck Disability Index (NDI) were taken two weeks post-study and at a one-month follow-up. Results showed both groups experienced reductions in NPRS and NDI disability scores at the second-week evaluation with p <0.001. However, there were no significant differences in NPRS and NDI scores at the one-month follow-up (NDI p=0.620 and 0.319; NPRS p=0.705 and 0.206). The intervention group showed better results at the second-week evaluation with NPRS p=0.005 and NDI p <0.001, but not at the one-month follow-up with NPRS p=0.984 and NDI p=0.280. Thus, adding DN to PIR is more effective in reducing pain and disability in non-specific neck pain among office workers.